2010
DOI: 10.1177/0956797609359908
|View full text |Cite
|
Sign up to set email alerts
|

What Counts as a Choice?

Abstract: People everywhere select among multiple alternatives, but are they always making choices? In five studies, we found that people in U.S. American contexts, where the disjoint model of agency is prevalent, are more likely than those in Indian contexts to construe their own and other individuals' behaviors as choices, to construe ongoing behaviors and behaviors recalled from memory as choices, to construe naturally occurring and experimentally controlled behaviors as choices, to construe mundane and important act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
47
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(49 citation statements)
references
References 21 publications
2
47
0
Order By: Relevance
“…As for the term ''decision," we will refer to a commitment to a course of action that is intended to serve the interests and values of particular people (Yates & Potorowski, 2012). In our experience, it is rare for people's everyday characterizations of decisions to conflict with the definition used here, although people of different cultures may disagree on whether a given specific event constitutes a decision (Savani, Markus, Naidu, Kumar, & Berlia, 2010).…”
Section: Introductionmentioning
confidence: 75%
“…As for the term ''decision," we will refer to a commitment to a course of action that is intended to serve the interests and values of particular people (Yates & Potorowski, 2012). In our experience, it is rare for people's everyday characterizations of decisions to conflict with the definition used here, although people of different cultures may disagree on whether a given specific event constitutes a decision (Savani, Markus, Naidu, Kumar, & Berlia, 2010).…”
Section: Introductionmentioning
confidence: 75%
“…Previous studies have shown that family member’s influence, which may be seen as a restriction of personal freedom in the West, may be internalized and act as powerful motivational force for people in East Asia (Iyengar and Lepper, 1999; Brew et al, 2001; Savani et al, 2010; Fu and Markus, 2014). Our investigation expands on these findings, as it suggests that, even for very important personal decisions such as workplace choice, the value attached to others’ opinions differs across cultures, and is greater for Japanese than for Westerners.…”
Section: Discussionmentioning
confidence: 99%
“…Joshi, 1995). A series of studies by Savani and colleagues also indicate that the discourses of control and “choosing according to one’s personal preferences may not be as important to the experience of agency for Indians as it is for North Americans” (Savani et al, 2008, p. 861; Savani et al, 2010, 2011). …”
Section: Introductionmentioning
confidence: 99%